The 4th Industrial Revolution: contemplations on curriculum review and its implementation in the Malaysian higher education institutes - Abdul Majid, Faizah; Md Zamin, Ainul Azmin (Universiti Sultan Azlan Shah, 2019)
The higher education landscape is once again undergoing massive transformation. Not more than two decades ago, it was the advancement of digital technology and globalization that drove the need for transformation in higher education. At present, the transformation is driven by the need to face the challenges of the 4th Industrial Revolution (4IR). Much discourse has been centered on debating the roles of higher education in meeting the demands of 4IR. This paper aims to address similar issue by discussing the curriculum reviews done by higher education institutes in embracing 4IR. As curriculum is central to any academic programs, it is vital that the curriculum review done by the higher education institutes in catering to the growing needs of 4IR be examined. The close look at the curriculum review initiatives will focus on the changes done in terms of subject contents, methods of delivery and methods of assessment. Further, the academics’ perceptions of the curriculum review and how the curriculum is to be implemented are investigated. The findings shed some lights on the contemplations of the academics amidst the initiative to provide higher education curriculum that meet the requirements of the Ministry of Education and the needs of 4IR. It is expected that curriculum departments in the higher education institutes could find the findings useful in bridging the gap between the academics’ concerns and the need to meet the challenges of 4IR through the revised curriculum implementation.